Professor Elżbieta Szczot at the John Paul II Catholic University of Lublin (1965–2024) – In Pursuit of Truth: a Scholarly Life Guided by Faith and Reason - Kędracka, Malwina (Philosophy and Canon Law, 2024)
This article is a tribute to and a concise presentation of the scholarly, didactic, and social-organizational activity of Professor Elżbieta Szczot (1965–2024), a long-time staff member of the Faculty of Law, Canon Law and Administration at the John Paul II Catholic University of Lublin. She was an outstanding expert in the field of law, especially canon law, as well as a respected teacher and mentor to many generations of students. The text highlights the key areas of her research interests – from the law of the holy sacraments and the protection of marriage and the family, to issues related to European integration and the specific policies of the European Union. In her pursuit of academic truth, Professor Szczot harmonized faith and reason, remaining until the end a hardworking and humble person. Despite her illness, she did not cease her scientific activity. She passed away on March 10, 2024, in Warsaw, after a long and serious illness.